Professional development and teacher self-efficacy: Learning from Indonesian modern Islamic boarding schools - Othman, Azam; Masum, Ali (Universitepark, 2017)
This study highlights teachers’ involvement in professional development (PD) activities teachers in the Darussalam Modern Islamic Boarding School (DMIBS), East Java, Indonesia. It evaluates the implementation of PD programs by identifying teachers` perception toward PD they participated in. The study used a survey research approach to investigate professional development and the level of teacher`s self-efficacy at the boarding school. The majority of teachers have a high level of satisfaction toward the implementation of PD activities in DMIBS in terms of course content, instructor, relevancy to teaching practice and course management. Also, teachers reported that the school had given them an adequate opportunity to participate in different types of PD activities. However, the study did not find significant differences between the length of teaching experience and teachers’ academic qualifications in teachers` perceptions towards PD activities. Some studies found that teachers with higher levels of academic qualification, showed higher and increased levels of efficacy. However, the current study did not show similar results as teachers with degrees and DMIBS qualifications respectively showed no significant differences in their levels of efficacy. This indicates that having different academic qualifications did not affect the increase in teachers` efficacy.